Peningkatan Keterampilan Berbicara dengan Penerapan Metode Bermain Peran pada Siswa Kelas III SD Negeri 060904 Multatuli - Rambe, Riris Nurkholida; ‘Arif, Muhammad (ANWARUL, 2023)
The objectives of this research are 1) Increasing teacher skills in learning Indonesian by using role playing methods, 2) Increasing learning activities of students by learning Indonesian with role playing methods, 3) Improving student learning outcomes in Indonesian learning with using the role playing method. This type of research is action research. The research subjects were teachers and all fourth grade students of SDN 02 Gidangelo 2018/2019 academic year. The samples taken were 29 fourth grade students using data in this study obtained through tests, observations, and documentation. The results of the study revealed that there was an increase in the acquisition of the value of speaking skills. In pratindakan the average value of 65.80 and the number of students completeness by 31%. Then in the first cycle applied the role playing method obtained an average value of 75.86 and the total completeness of students was 62%. That is, the use of the Role Playing method can improve the speaking ability of students, but the results obtained have not exceeded the target determined by the researcher so that it is continued in the second cycle. In the second cycle, the average score of 84.77 and the total completeness of students was 72%. In conclusion, the Role Playing method can improve students' speaking abilities.